Simulation Analysis of the Influence of Variation in Some Selected Design and Control Parameters on the Acceleration Time of a Turbojet Engine - Orkisz, M. (Engineering Transactions, 1991)
The equation governing the acceleration time of a turbojet engine is presented in an implicit form; expansion into power series contains first order partial derivatives. The derivatives represent the "sensitivity measure" of the acceleration time to the variation of a) -the design parameters of the compressor (stability margin, moment of inertial, efficiency, compression ratio), b) -technical conditions (deformation of blade profiles, due to erosion, turbine blade clearance), c) -service conditions due to flight speed and altitude. The relations derived enable the wide range simulation analysis of the problem.